Avaliação da distribuição espacial do ruído em máquinas agrícolas - Silveira, Walisson Marques (2023)
Agricultural machines are necessary in all stages of cultivation in crops, causing the operator to spend long hours handling the machine, thus causing occupational problems, including exposure to noise transmitted by the machine. The present work aims to evaluate the spatial distribution of noise in agricultural machinery, in order to generate maps with points of greater and lesser incidence, as well as their distance away from the noise. The work was carried out in the experimental area of the Laboratory of Investigation of Accidents with Agricultural Machines (LIMA), of the Department of Agricultural Engineering of the Center of Agricultural Sciences of the Federal University of Ceará. The machines used were Valtra tractors models A950, BM120, BM125i and an Agritech tractor, model TC14; implements were also evaluated: a brushcutter, a rotary hoe, a front brushcutter, a corrective spreader and a pneumatic seeder, all (except the front brushcutter, which was coupled to the motor cultivator) coupled to the A950 tractor. Data were collected with each machine at its nominal work speed and the implements at a nominal speed equivalent to 540 rpm of the PTO. Noise evaluations were carried out using a decibel meter around each machine, positioned in the center of a flat area, without obstacles with dimensions of 9 x 9 meters, totaling 100 points, where from these, noise maps were generated. noise, using the Surfer® program. In addition to these measurements, evaluations of the noise distance radius were carried out, with the collection of points at a distance of ten meters in front, behind, to the right and to the left of the center of the machine. Data were submitted to Pearson's correlation coefficient analysis. It was observed that the areas closest to the engine exhaust system and the moving parts emit more noise than the others, making it necessary to use ear protection and control the time of exposure to this noise, as well as the use of of alternatives to reduce this noise. The knowledge of the areas where the noise may propagate, as well as the use of mapping programs is a good tool for the best visualization to detect the origin of the noise and subsequent decision making.